SIMONE: A Simulator for Interruptions and Message Overload in Network Environments. (10th March 2009) - Gupta, Ashish; Sharda, Ramesh
This study describes Simulator for Interruptions and Message Overload in Network Environments (SIMONE), a model that simulates the flow of e-mail within a network of Knowledge Workers (KWs). The simulation model can help devise coping mechanisms to mitigate two important managerial problems, information overload and interruptions associated with e-mails. We discuss the need for developing such a model, describe various analytical, logical and implementation components, Finally, results of simulation experiments are discussed along with implications for future research. The results show that scheduling e-mail processing times across an organisation can reduce interruptions due to continual e-mail arrivals.